Are We Ready for Epitope-Based HLA Matching in Clinical Organ Transplantation?. Issue 8 (August 2017) - Duquesnoy, Rene J.
Abstract : Abstract: This overview describes recent developments demonstrating the significance of epitopes in HLA antibody responses and matching for organ transplantation. HLA epitopes are defined by molecular modeling and amino acid comparisons between HLA alleles and the HLAMatchmaker algorithm considers eplets as essential components. Each allele represents a distinct string of eplets and matching is done by aligning donor and recipient strings. Evidence is summarized how mismatched eplet loads affect antibody responses and transplant outcomes. Epitope-based matching has been applied not only to identify acceptable mismatches for sensitized transplant candidates but also to identify more suitably mismatched donors for nonsensitized patients. Three recently proposed theories will further our understanding of the immunogenicity of individual HLA eplets. It has become apparent that epitope-based matching is superior to antigen matching; we should be ready soon to apply this principle in the clinical transplant setting very soon. Abstract : This review describes recent developments, challenges and clinical application of HLA epitope-based matching aiming to identify acceptable mismatches for sensitized transplant candidates and more suitably mismatched donors for nonsensitized patients, thus allowing more transplants and reducing HLA sensitization.